Language Disorder of the Child with Autism in The Gentle Life’s Youtube Channel - Sindi Pebriani; Udayani Permanaludin; Toneng Listiani (Journal of English Language and Education, 2026)
This study examines language disorder in a five-year-old child with Autism Spectrum Disorder (ASD), named Mikko, as observed in natural communication settings on The Gentle Life YouTube channel. Language is an essential part of everyday communication; however, children with ASD often experience difficulties in both understanding and producing language. While previous studies have widely explored language disorders in autism, most have been conducted in clinical contexts, providing limited insight into how these difficulties appear in real-life interactions. This study aims to identify the types of language disorder and analyse how they are expressed in natural communication using the perspective of Weak Central Coherence Theory. A qualitative case study design is employed, focusing on naturally occurring utterances produced by the participant. The findings reveal that Mikko demonstrates various language disorder features, with pragmatic impairment as the most dominant, followed by echolalia, syntactic irregularities, and limited vocabulary development. These patterns indicate that her communication is strongly influenced by a detail-focused cognitive processing style, which affects her ability to produce contextually appropriate and meaningful language.